Differential adherence capacities of clinical isolates of Streptococcus pneumoniae at different growth states to human respiratory epithelial cells (in vitro) - Mohd Desa, Mohd Nasir; Parasakthi, Navaratnam; Vadivelu, Jamunarani; Sekaran, Shamala Devi (Academic Journals, 2008)
This study was conducted to evaluate the adherence and invasion capacity of four clinically important pneumococcal serotypes at early-, mid- and late-log phases at 1 and 3 h incubation times to A549 cells-a human respiratory epithelial cell. We observed that adherence capacity varied among the different isolates at all growth phases (pi 0.05) but generally, an individual isolate had a comparable adherence capacity at all levels of the log phase (p>0.05). Bacterial adherence also increased after a longer exposure to the host cells but significant differences were mostly observed at only early- and late-log phases at both incubation times. No bacterial invasion was however observed at 1 h post incubation but that at 3 h, a few bacteria penetrated the host cells but the bacterial cfu numbers were statistically insufficient for analysis. More studies are required to further confirm these observations. Streptococcus pneumoniae, epithelial cell, adherence, invasion, exponential growth phase.